Neural Network Energy Control of Combustion Engines for Automotive Software Applications - Silva, Marcos Henrique Carvalho; Maggio, André Vinícius Oliveira; Laganá, Armando Antônio Maria; Filho, João Francisco Justo; Pereira, Bruno Silva; Moscardini, Demerson (Actas del Congreso Internacional de Ingeniería de Sistemas, 2024)
This article focuses on the application of neural network control for energy generation in an internal combustion engine. A two-layer neural network architecture was developed and tested using laboratory data obtained from a bench dynamometer to accurately identify the network’s parameters. The neural network is employed to establish an accurate correlation between the magnitude of actuation signals and the fundamental variables responsible for regulating energy generation within the system. The control system utilizes a gain-scheduling routine to adjust the controller’s gain, which attenuates the increment for low error values. An energy generation model is presented to design a virtual engine, enabling accurate control strategies. To ensure the safe operation of the engine, a safety routine is implemented to prevent the control action from assuming values that could negatively impact the vehicle’s response to the driver’s commands. The developed controller demonstrates a low average absolute error in steady-state conditions and a low average rise and fall time during transient states, ensuring both drivability and good engine performance. To enable the application in software, in structures such as hardware-in-the-loop simulation and engine control units, systems are implemented to ensure real-time operations.